2001
DOI: 10.1063/1.1353558
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale surface electrical properties of indium–tin–oxide films for organic light emitting diodes investigated by conducting atomic force microscopy

Abstract: Articles you may be interested inWork-function changes of treated indium-tin-oxide films for organic light-emitting diodes investigated using scanning surface-potential microscopy J. Appl. Phys. 97, 073713 (2005); 10.1063/1.1884245Highly oriented indium tin oxide films for high efficiency organic light-emitting diodes Nanoscale surface electrical properties of indium-tin-oxide films prepared by different cleaning methods for use as anode materials in organic light emitting diodes are studied by conducting atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Such a relationship is expected for unipolar memory behavior, and these regions are called recordable regions. However, in the regions where the current was less than 5 nA, the Fowler‐Nordheim electron tunneling mechanism (Chen et al, ; Lin et al, ) shown in Figure c was responsible for the detected current, and the turn‐on voltage was higher than 4 V; these regions are called insulating regions. The coverage percentages of these three regions, which are presented in Figure , were determined using the current distribution histograms of the current images in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a relationship is expected for unipolar memory behavior, and these regions are called recordable regions. However, in the regions where the current was less than 5 nA, the Fowler‐Nordheim electron tunneling mechanism (Chen et al, ; Lin et al, ) shown in Figure c was responsible for the detected current, and the turn‐on voltage was higher than 4 V; these regions are called insulating regions. The coverage percentages of these three regions, which are presented in Figure , were determined using the current distribution histograms of the current images in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The tips were precoated with a Cr layer and subsequently coated with a 20 nm PtIr film by ion sputtering. The CAFM and SSPM procedures employed in this study have been previously described (Chen, ; Chen et al, ; Lin et al, ; Yu et al, ). The current–voltage ( I – V ) curves and current maps were measured by applying a positive voltage to the tip while the substrate was grounded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of pre-cleaning prior to loading into the evaporation chamber consisted of soaking in ultra-sonic detergent for 30 min, spraying with de-ionized (DI) water for 10 min, soaking in ultrasonic DI water for 30 min, oven bake-dry for 1-2 h, and ITO surface stabilizing ultraviolet ozone illumination [19] for 9 min.…”
Section: Oled Fabricationmentioning
confidence: 99%
“…In this study, GaN films were grown using molecular beam epitaxy (MBE) on two different substrates, ZnO and sapphire. Atomic force microscopy (AFM), conducting atomic force microscopy (CAFM) (Chen, Hou, Hsieh, Chang, & Chen, ; Chen et al, ; Lin, Chen, Perng, & Chen, ; Yu et al, ), and scanning surface potential microscopy (SSPM) (Chen, ; Chen et al, ) were utilized to integrally study and analyse the differences in surface structure, contact current distribution, and work function (WF) distribution of the films. Differences in these microphysical characteristics could seriously affect the function and efficiency of GaN‐based components because they may result in the redistribution of the charges inside the GaN semiconductor, which form the built‐in electric field, while the quantum‐confined Stark effect could accelerate charge accumulation.…”
Section: Introductionmentioning
confidence: 99%